Local Marketing of a National Texting-Based Smoking Cessation Program: Is It Cost Effective? - Brown, Henry Shelton; Patel, Ujas; Seidel, Sarah; LeMaistre, Ashley; Wilson, Kim (Frontiers in Public Health, 2020)
Tailored texting interventions for smoking cessation are increasingly popular given the ubiquitousness of smart phones. Because high development costs and limited expertise may pose substantial barriers to designing and implementing these programs at the local level, utilization of existing programs at the national level is a promising strategy. In 2011, Austin Public Health focused on promoting smoking cessation among Austin/Travis County residents. Their strategy involved marketing and linking their citizens to a federally-funded, evidence-based smoking cessation program via texting. The target audience was low income, 18-24 year olds. Their marketing strategies included radio ads, digital ads, social media ads, and direct outreach at events in Austin, Texas. During the period between April 2016 and July 2017, 844 people signed up for the program. The quit rate was comparable to other texting programs which were tailored at the local level, and the program was cost-effective, costing $26,491 per life-year added, averting $75 per person in medical costs, discounted at 3%.